The importance of analytical methodology in accurate diagnosis and monitoring of intrahepatic cholestasis of pregnancy - Martinefski, Manuela Romina (2013)
The present case demonstrates the problematic results associated with routine liver tests and enzymatically determined serum total bile acids (TBA).The optimal way to diagnose intrahepatic cholestasis of pregnancy accurately and follow its progression is through evaluation of bile acid profile and serum TBA. In the present case, the determination of these parameters via capillary electrophoresis optimized management. Regular monitoring of this disease with adequate analytical methodology is important.